Factors Affecting Conservation of the Phuchomngea Forest Reserve by People in Xiangngern District LuangPrabang Province, Lao People’s Democratic Republic - Channang, Bounheuang; Sakkata, Phahol; Fongmul, Saisakul; Rungkawat, Nakarate (Community and Social Development Journal, 2022)
The objective of the study were to study 1) the personal characteristics, socio-economic. 2) Factors affecting conservation of Phuchomngea reserved forest in Xiangngern District, LuangPrabang Province, Lao People’s Democratic Republic. The study use interview technique by using sampling of 188 households. The tools used in this research consisted of questionnaires. The data analyzed by description. Statistical techniques were percentage, mean and multiple regression. Form the research finding, it was found that indicated 50.5% of the respondents were male with an average age of 40 years. The main education level of respondents was at primary school 39.9%, married 85.1%. They had been born in the present area 73.4%, and They resettle was period 30.17 years. The respondents were social group members 53.2%. They have attended training about forest conservation is 1.03 times, they perceive information on forest conservation an average of 4.79 times. They have experience on forest conservation an average 1.50 times per year. The average number of household member was 5.84. Their average month household income was 7,309.31 bahts. Agriculture was their main occupation and the average size of land holding was 29.87 rais. Most of them Participation in the activities of the forest reserve conservation was 1-2 time per year. Factors affecting the role of people in the forest reserve conservation were main household income, training on forest conservation, born in the present area and social group membership.